Análise dos fatores de riscos e comportamentos inseguros na constituição de incidentes e acidentes de trabalho - Sousa, Francisco Formiga de (2015)
Over the past decades, alternative views to the traditional approach of occupational accidents have emerged, fact that expands the perimeter of analyzes and paves the way to questioning about the assumptions concerning concepts of security in the work environment. Therefore, this study aims to describe the relationship of risk factors and unsafe behavior in the constitution of incidents and accidents at work, during the period of 2012-2014 in the production sector of a food factory in the state of Paraíba. The obtained results, by means of mathematical modeling based on Multiple Linear Regression Models, showed that occupational accidents and incidents are explained by a coefficient of determination of 63,55%, by the risk factors and the unsafe behaviors caused by workers. However, when analyzing the correlation between unsafe behaviors due to the risk factors, it was obtained a coefficient of determination of 38% characterized as a low correlation among the observed variables; such fact is enhanced by the perception of workers, analyzed by Hypothesis Test for Proportion with α = 5% (significance level), which identified that only two risk factors – environment temperature and discomfort when using Personal Protective Equipment (PPE) – have a strong association with the unsafe behaviors of removing the arms protectors, gloves and face shield during operational activities. In spite of that, it was found that there is a strong association between these two risk factors, which allowed significant conclusions.